Challenges of Clerkship of Public Health in Golestan Medical University; A Qualitative Study - alireza heidari; Javad khademi; zahra Khatirnamani; Narges Rafiei; Mehdi Abbas Abadi; A Charkazi; SMR. Ghanbari; SK Mirkarimi; Maghsoudlou; M Lotfi; M Sohrabi (Babol University of Medical Sciences, 2022)
Background and Objective: An internship course in the field gives students the opportunity to put what they have learned into practice; it allows students to understand and try to address potential shortcomings. It also increases their potential for future employment. The purpose of this study was to determine the challenges of internship training program in the field of public health in the School of Health of Golestan University of Medical Sciences. Methods: This qualitative study will be conducted in 2019-2020 with inductive content analysis approach in Golestan province. Participants in the study were 31 undergraduate public health graduates who completed their internship at the School of Public Health, undergraduate public health students who had completed at least one semester of internship, instructors, and faculty members of the Department of Public Health. They were purposefully selected. Data were collected by group and individual interviews and analyzed by content analysis method and Atlas.ti 8 software. Findings: Challenges of internship in the field of public health were explained in 6 main thems (education system, students, pre-internship planning and preparation, internship management, internship field, student monitoring and evaluation) and 23 sub-thems. Conclusion: The need to pay more attention to the weaknesses of the internship resulting from the study and selection of appropriate strategies to improve the current situation in the framework of the operational plan, can lead to quantitative and qualitative improvement of internship in public health at Golestan University of Medical Sciences.